Interreligious Cooperation for Family Values: Latvian Experience - Zbigņevs Stankevičs (Chrześcijaństwo-Świat-Polityka)
The stimulus for writing the paper was an invitation to participate in the academic conference “St. John Paul II’s natural law legacy and international human rights: toward a century of persuasion”, organized by Cardinal Stefan Wyszynski University and Ave Maria International School of Law. I offered to share the Latvian experience of the last twenty-five years in the field of the defence of family values, taking into account cooperation between different religious communities in Latvia.